Chemical vapor deposition growth and transfer of two-dimensional hexagonal boron nitride - Chin, Warren Chee How (2015)
Atomically thin two-dimensional (2D) hexagonal boron nitride (h-BN) exhibits many attractive properties such as high thermal conductivity, stability, high mechanical performance, good electrical insulator which is also chemically inert and resistant to corrosion. This report consist of literature review summarizing the structure and properties on 2D h-BN, its synthesis methodologies and transfer methods to extract the film onto other substrates. Different types of characterisation tools were also used namely Raman spectroscopy, SEM, AFM and four-point probe to verify the properties of the grown h-BN. In this report, controllable growth of monolayer 2D h-BN films on copper substrates through chemical vapor deposition using ammonia borane as precursor is demonstrated. A transfer process is necessary for the film to be use for subsequent device fabrication and for further characterisation. These films are traditionally transferred using a conventional wet transfer process. Here, we explore another transfer method known as “bubbling transfer” to extract the film onto other substrates. Besides improving the yield of the transferred h-BN film, this transfer technique results in lesser impurities by optical inspection and enable recyclability of the copper substrates.